Optical Manipulation of Fibroblasts with Femtosecond Pulse and CW Laser - Xia Zhang; Yi Wu; Siao Cai; Guoying Feng (Photonics, 2024)
Using tight focusing light, optical tweezers (OT) are tools that can manipulate and capture microscopic particles and biological cells as well as characterize a wide range of micro and nanomaterials. In this paper, we focused on fibroblasts, which are widely used in the biomedical area for a variety of purposes, including promoting human wound healing and preventing the early proliferation of tumor cells. We first built an optical tweezer experimental platform, using an 808 nm continuous-wave laser as the capture light source, to confirm that the device can precisely control the movement of single or multiple particles as well as fibroblasts. Then, a 1030 nm femtosecond laser was employed as the capture light source to study the manipulation of microparticles and fibroblasts at different powers. Lastly, a protracted manipulation protocol was used to prevent the fibroblasts from adhering to the wall. This method can be used to isolate and precisely block adherent growth of fibroblasts in cell populations. This experimental result can be further extended to other biological cells.